Students’ concentration in online English classes: Main factor and solution at UTAR Kampar campus - Khoo, Jia Huey (2022)
This research presents the students’ concentration in online English classes: Main factor and solution at UTAR Kampar campus. The first research objective is to identify the main factor that causes the UTAR ED and EL students to lose concentration in the online English lessons. The second research objective is to determine the strategies that the English lecturers and tutors can do to make students stay focused in online English lessons from the perspectives of UTAR ED and EL students. The findings from this research show that ED and EL students from UTAR Kampar mainly lose focus due to the environmental factor while the strategies that educators can do is to have two-way communication in the online English classrooms. This study enables the stakeholders to understand more about the reasons of students losing concentration on the online English lessons. Furthermore, allowing the educators to know the teaching methods that are preferred by the students in staying focused. To improve the students’ concentration in online English classes, all the stakeholders must play their part so that the students can learn English more effectively in online environment.